Avionics ICD representation using JSON for Configurable Data Analyzer - Sasikumar, Aleena; Prem, N; Satyanarayana, JV (2019 International Conference on Range Technology (ICORT), 2019)
The Interface Control Document(ICD) represents the details of information being transferred between the avionics subsystems during its different phases of operation. The ICD is generated as a result of meticulous study on the subsystems and their interfaces during System architecture and design. It is usually in the .doc and .pdf format which is rarely machine-understandable, due to lack of standard templates and notations for identifying the data types and encoding mechanism. The ICDs are written for human understanding and not for software. The ICD information is implemented in the form of data decoding and encoding in many OnBoard software, test support and utility software of the avionics project and hence the ICD becomes the core point of changes for all those software applications during the project lifecycle. Changes in the ICD leads to changes in a number of software applications; which in turn leads to software updates, testing and validation in the short span of time. This paper covers the technique of entering the ICD information, representation of ICD and saving in the JSON format. JSON-Java Script Object Notation is both human and computer understandable format and the benefits of using it is covered in this paper. Configurable software is one that can be configured to run differently to meet different types of needs, instead of changing the lines of code and making different builds and versions. The machine understandable representation of ICD is a remarkable achievement, since it is the first step to auto-code generation, configurable software development and test automation; finally all these are going to cut short the overall project cost and time. Quick development of generic avionics data analysis software and telemetry display software are already proven and deployed successfully using this technique.